2014
DOI: 10.2478/s13380-014-0223-9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in research on the neural basis of „chemobrain”

Abstract: Cancer survivors treated with chemotherapy frequently complain about impairment of cognitive functions including attention and memory. While the contribution of factors like psychological distress, anxiety or fatigue to this "chemobrain" syndrome has been discussed, studies in rodents have demonstrated the toxicity of various chemotherapeutic substances to the adult central nervous system. In humans, structural brain imaging has revealed both reduced gray and white matter volume and decreased white matter inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Kaiser et al and Pomykala et al concluded from their studies that structural brain imaging, incorporating volumetric and DTI analyses, disclosed diminished gray and white matter volume, as well as reduced white matter integrity persisting from months to years after chemotherapy. This supports the proposition that structural brain alterations observed post-chemotherapy are indeed a consequence of exposure to chemotherapeutic agents ( 44 , 45 ). Another investigation, comparing the brains of breast cancer survivors exposed to chemotherapy with those of healthy women, assessed the long-term impact of chemotherapy on brain microstructural integrity.…”
Section: Discussionsupporting
confidence: 87%
“…Kaiser et al and Pomykala et al concluded from their studies that structural brain imaging, incorporating volumetric and DTI analyses, disclosed diminished gray and white matter volume, as well as reduced white matter integrity persisting from months to years after chemotherapy. This supports the proposition that structural brain alterations observed post-chemotherapy are indeed a consequence of exposure to chemotherapeutic agents ( 44 , 45 ). Another investigation, comparing the brains of breast cancer survivors exposed to chemotherapy with those of healthy women, assessed the long-term impact of chemotherapy on brain microstructural integrity.…”
Section: Discussionsupporting
confidence: 87%
“…Preclinical research Preclinical studies have provided some insights into the pathophysiological mechanisms underlying CRCI associated with nontargeted delivery of chemotherapy. [85][86][87][88] It has been shown in animal models that cytostatic agents from different classes (eg, antimetabolites, DNA cross-linking agents, and alkylating agents) administered peripherally and in clinically relevant dosages can disrupt various neurobiological processes and induce cognitive impairment. 49 A direct toxic effect of chemotherapeutic agents on various cell populations has been proposed as etiology for these neurotoxicities.…”
Section: Pathophysiological Underpinningsmentioning
confidence: 99%
“…In addition, cognitive deficits have also been described in cancer patients prior to chemotherapy ( Ahles and Saykin, 2002 ). In recent years, several studies using neuroimaging techniques, concretely magnetic resonance imaging (MRI) and positron emission tomography, as well as event-related brain potentials (ERPs), have reported structural and functional changes associated with cancer and chemotherapy ( Simo et al, 2015 , Kaiser and Dietrich, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fined-grained analysis of electrophysiological measures (such as ERPs), widely used in cognitive neuroscience, allows us to functionally characterize certain cognitive processes with higher temporal precision when compared to other metabolic based neuroimaging techniques ( Münte et al, 2001 , Marco-Pallares et al, 2009 ). However, ERPs have been scarcely used to investigate the neural correlates underlying cancer and chemotherapy-related cognitive impairments (see for a review, Kaiser and Dietrich (2014) ). Most of the ERPs studies focused on cancer population yielded converging evidence of changes in the well-known P300 attention-related component associated with chemotherapy ( Kreukels et al, 2005 , Kreukels et al, 2006 , Kreukels et al, 2008a , Kreukels et al, 2008b , Heukrodt et al, 1988 , Kam et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%